City, heritage and environment: crossed lukeds (REVISTA NODO, 2019)
This article discusses the pertinence between the conservation practices of cultural heritage and the discussions about the environmental problems that especially afflict the great metropolis in the contemporary scenario. The development of the narrative details key concepts, composing a multifaceted framework, based on studies from authors that refer to international documents, exploring different approaches related to the topic. The Recovery Plan for the Historic Centre of Bologna (1971-1984) allows for arguments on contemporary agenda issues regarding the preservation of cultural and environmental heritage.
Keywords: Heritage; Nature; Culture; Environmental preservation